A study on the importance of casino gambling as a motivator for Asians to cruise. - Gwee, Rong Rong. (2008)
A review of the literature revealed that casino gambling is an important motivator for Asians to cruise. Furthermore, there is an inverse relationship between casino gambling and the cruiser's position on the level of the Travel Career Ladder. However, the results showed that casino gambling is not an important motivator and there is positive but weak relationship between casino gambling and the cruiser's position on the TRavel Career Ladder.